SOSIALISASI PENERAPAN POLA HIDUP SEHAT DI ERA NEW NORMAL PADA PEKON BANDUNG BARU (LP3K Lampung, 2021)
The COVID-19 pandemic is getting more serious as the increasing number of Indonesians exposed to COVID-19, now the international world is also confused about the problem of this COVID-19 pandemic. The general objective of this Community Service activity is to help the Pekon Bandung Baru community in overcoming current problems in improving and maintaining health by adopting a healthy lifestyle. The method that will be used in this community service is through socialization activities so that the Pekon Bandung Baru community can adopt a healthy lifestyle. In addition, providing trainings in maintaining and maintaining a healthy body to avoid various diseases. Health education is the same as public health education, which is an activity or effort to convey health messages to the community, groups or individuals. The socialization of the implementation of a healthy lifestyle in the new normal era is expected to increase the awareness of the New Bandung community of the importance of maintaining a healthy lifestyle and always following health protocols.